PHYSIOTHERAPY MANAGEMENT OF ULCUS DECUBITUS AT RSU 'AISYIYAH PONOROGO HOSPITAL - A CASE STUDY - Widyawati, Erinda Anggar Tri; Perdana, Suryo Saputra; Setiyawan, Agus (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Ulcus Decubitus is a condition that is serious with figures of morbidity an mortality in the age of advanced and would be a burden families with the cost of high care. Ulcer sores can occur at any stage of the age, but the case is a matter which specific ally on advanced age due to immobilization. Specificity lies in the incidence of even that are closely related to immobilization which is a problem major in patients geriatric1. The patient slipped about 8 months ago, since then the patient has been unable to walk and move. The left leg hurts to move, and until now it's getting stiffer and can't be straightened, then a wound appears on the top of the left leg. At first it was just red and like a blister, but as time went on the wound became wet, Case Presentation: The method used in this study is a case report of one patient at RSU ‘Aisyiyah Ponorogo Hospital with identity Mrs.P with the age of 98 years. Management and outcome: The provision of positioning, active passive exercise and TENS is one of the effective methods to reduce complaints of pain due to ulcus decubitus. Discussion: One of the actions to reduce the incidence of pressure sores is by giving the side position. The reason for giving the tilted position is because this position is able to prevent the skin from rubbing and tearing the tissue, thereby reducing the incidence of pressure sores2. According to the researcher, the tilted position also has advantages, namely it does not take much time and is easy to implement, tools and materials are easy to obtain and the patient's waiting family can carry out their own in reducing the patient's pressure sores3. Conclusion: Handling physiotherapy in the form of positioning, active passive exercise and TENS can reduce pain complaints that Mrs.P.